Extending measurement range for three-dimensional structured light imaging with digital exponential fringe pattern - Abel, Kamagara (The 2nd Annual Higher Education Conference, Hotel Africana Kampala, Uganda, 2020)
In this paper, a method and an approach for intrinsically extending the measurement range for digital fringe projection profilometry with structured light imaging techniques is presented. This approach exploits the fact that at low levels of defocusing, exponential binary-coded fringe pattern exhibits a quasi-sinusoidal form having intact binary structures with reduced or negligible errors owing to high-order harmonic robustness during fringe generation. Experimental simulations and results show that within the desired region of defocus or at an extended measurement range, the proposed method exhibits a 45% comparative reduction in root-mean-square phase error hence improvement in final measurement result.